An implementation of rock engineering system (RES) for ranking the instability potential of slopes in Greek territory. An application in Tsakona area (Peloponnese - prefecture of Arcadia) - Tavoularis, N.; Koumantakis, I.; Rozos, D.; Koukis, G. (Bulletin of the Geological Society of Greece, 2015)
This paper presents an application of the Rock Engineering system (RES) in an attempt to assess the inherent instability potential of Tsakona landslide in the region of SW Arcadia, Peloponnese, Greece which happened on February 2003. The RESystem has been considered to fulfill the basic requirements to deal with landslide phenomena, as it combines objectivity and efficiency. The main scope of RES application to landslide studying is to define the important causative and triggering factors responsible for the slope failures, quantify their interactions, obtain their weighted coefficients and calculate the instability index, which refers to the potential instability of the examined natural slope. In this study, the final implementation of the RES method is achieved through an interaction matrix, where ten principal parameters were selected as controlling factors for the landslide occurrence. It is concluded that RES could be a simple and efficient tool in calculating the instability index and as a consequence getting a prognosis of a potential slope failure regarding the land use and development planning processes in landslide susceptible areas.